Humoral immune response to authentic circulating severe acute respiratory syndrome coronavirus 2 variants elicited by booster vaccination with distinct receptor‐binding domain subunits in mice. Issue 9 (3rd June 2022) - Jiang, Yushan; Zhang, Huan; Yu, Jianhai; Huang, Dong; Zhai, Linlin; Li, Mengjun; Wang, Yuelin; Ren, Zuning; Zou, Lirong; Zheng, Zhonghua; Hu, Huanyu; Zhang, Junfang; et al.
Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) variants could induce immune escape by mutations of the spike protein which are threatening to weaken vaccine efficacy. A booster vaccination is expected to increase the humoral immune response against SARS‐CoV‐2 variants in the population. We showed that immunization with two doses of wild type receptor‐binding domain (RBD) protein, and booster vaccination with wild type or variant RBD protein all significantly increased binding and neutralizing antibody titers against wild type SARS‐CoV‐2 and its variants in mice. Only the booster immunization by Omicron (BA.1)RBD induced a strong antibody titer against the omicron virus strain and comparable antibody titers against all the other virus strains. These findings might shed the light on coronavirus disease 2019 booster immunogens.